Vernacular architecture and cultural landscapes in the Sondondo valley (Perú) - Sáez, Elia (2020)
Sondondo is an inter-Andean valley located between 3,500 and 4,500 meters above sea level. Inhabited, transformed and modelled since ancient times by the local rural communities, an extraordinary cultural landscape has been created through their particular relationship with the environment. Since the pre-Hispanic settlements (Wari 600 AD), through colonial indigenous “reductions”, to the villages of vernacular architecture, which are at the foundation of contemporary populated centres, the territory has been variously and successively settled, inhabited and transformed. Its vernacular architecture has evolved at multiple scales, from domestic architecture to urban structures. It has created spaces for agriculture and livestock herding, and the spectacular agricultural andenerías (farming platforms and terraces) that have shaped the territory for centuries. The latter simultaneously developed irrigation infrastructures and techniques. The result is a landscape of great plastic effects, in a geographical setting bordered by the apus – tutelar mountains – traditionally “sacralized” by the Andean cultures. Such enormous architectural-landscape legacy is now threatened by imported global models of false modernity disrupting the fragile balance of lifestyles and territories. The objective of this research project, ongoing since 2016, is to assess this territory, catalogue its vernacular architecture and landscape units. It also aims to propose projects and initiatives for sustainable local development. The work has been made available to the Ministry of Culture of Peru to support its request before UNESCO to include the site in its World Heritage List